2014
DOI: 10.1016/s0140-6736(13)62422-8
|View full text |Cite|
|
Sign up to set email alerts
|

Pathological complete response and long-term clinical benefit in breast cancer: the CTNeoBC pooled analysis

Abstract: US Food and Drug Administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

154
2,943
20
100

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 3,695 publications
(3,406 citation statements)
references
References 26 publications
154
2,943
20
100
Order By: Relevance
“…A previous report of the NeoAdjuvant Lapatinib and/or Trastuzumab Treatment Optimisation (NeoALTTO) phase III, randomized trial showed that dual anti-HER2 blockade with lapatinib and trastuzumab combined with weekly paclitaxel significantly increased the rate of pathological complete response (pCR) compared to trastuzumab and weekly paclitaxel (51·3% vs. 29·5% respectively; p= 0·0001) (7). In a recent meta-analysis funded by the US Food and Drug Administration (FDA) involving 11·955 patients, reaching pCR after neoadjuvant therapy was significantly associated with better event-free survival (EFS) and overall survival (OS), particularly in the HER2-positive population (N= 1·989) irrespective of hormone receptor status (Hazard Ratio (HR) 0·39 for EFS and HR 0·34 for OS) (8).…”
Section: Introductionmentioning
confidence: 99%
“…A previous report of the NeoAdjuvant Lapatinib and/or Trastuzumab Treatment Optimisation (NeoALTTO) phase III, randomized trial showed that dual anti-HER2 blockade with lapatinib and trastuzumab combined with weekly paclitaxel significantly increased the rate of pathological complete response (pCR) compared to trastuzumab and weekly paclitaxel (51·3% vs. 29·5% respectively; p= 0·0001) (7). In a recent meta-analysis funded by the US Food and Drug Administration (FDA) involving 11·955 patients, reaching pCR after neoadjuvant therapy was significantly associated with better event-free survival (EFS) and overall survival (OS), particularly in the HER2-positive population (N= 1·989) irrespective of hormone receptor status (Hazard Ratio (HR) 0·39 for EFS and HR 0·34 for OS) (8).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the achievement of pCR represents the main prerequisite to improve both disease-free survival and overall survival (OS) [20]. Several studies have shown that higher TIL infiltration in the pretreatment core biopsy specimen is a predictor of response to neoadjuvant chemotherapy [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, several previous studies of miRNA expression profiles of neoadjuvant chemotherapy for patients with HER2-positive breast cancer did not classify patients according to hormone receptor status (34,35). The pathological response and survival benefit of neoadjuvant chemotherapy with trastuzumab reportedly differs between two HER2-positive subtypes divided by hormone receptor status (10). Therefore, we classified HER2-positive breast cancer into subtypes based on ER status and subsequently analyzed miRNA expression.…”
Section: Discussionmentioning
confidence: 97%
“…However, there exists a discrepancy in the pathological responses and survival benefits of neoadjuvant chemotherapy between these two HER2-positive subtypes (10). Therefore, Usefulness of miRNA profiles for predicting pathological responses to neoadjuvant chemotherapy in patients with human epidermal growth factor receptor 2-positive breast cancer new predictive markers in combination with conventional markers, including immunohistochemical ER and HER2 status, are required.…”
Section: Introductionmentioning
confidence: 99%